LEGITIMIZATION OF JERUSALEM EMBASSY ACT ACCORDING TO INTERNATIONAL LAW - Riktin Noviani; Garry Gumelar Pratama (Diponegoro Law Review, 2021)
Jerusalem is a special entity under the administrative power of United Nations according to United Nations General Assembly Resolution 181, where Jerusalem does not fall under the sovereignty of any state. Jerusalem Embassy Act is the public law of United States which recognized Jerusalem as the capital city of Israel by establishing a diplomatic mission in the city.This paper concludes that Jerusalem Embassy Act is illegitimate according to international law. It turns its back to international obligation under the Vienna Convention on Diplomatic Relations 1961 and UN resolutions.Thus, the Jerusalem Embassy Act has to be pulled back by the US parliament in order to maintain international peace and security, bearing in mind the ongoing dispute between Palestine and Israel.